Midgut barriers prevent the replication and dissemination of the yellow fever vaccine in Aedes aegypti. - Lucie Danet; Guillaume Beauclair; Michèle Berthet; Gonzalo Moratorio; Ségolène Gracias; Frédéric Tangy; Valérie Choumet; Nolwenn Jouvenet (Public Library of Science (PLoS), 2019)
Background To be transmitted to vertebrate hosts via the saliva of their vectors, arthropod-borne viruses have to cross several barriers in the mosquito body, including the midgut infection and escape barriers. Yellow fever virus (YFV) belongs to the genus Flavivirus, which includes human viruses transmitted by Aedes mosquitoes, such as dengue and Zika viruses. The live-attenuated YFV-17D vaccine has been used safely and efficiently on a large scale since the end of World War II. Early studies have shown, using viral titration from salivary glands of infected mosquitoes, that YFV-17D can infect Aedes aegypti midgut, but does not disseminate to other tissues. Methodology/principal findings Here, we re-visited this issue using a panel of techniques, such as RT-qPCR, Western blot, immunofluorescence and titration assays. We showed that YFV-17D replication was not efficient in Aedes aegypti midgut, as compared to the clinical isolate YFV-Dakar. Viruses that replicated in the midgut failed to disseminate to secondary organs. When injected into the thorax of mosquitoes, viruses succeeded in replicating into midgut-associated tissues, suggesting that, during natural infection, the block for YFV-17D replication occurs at the basal membrane of the midgut. Conclusions/significance The two barriers associated with Ae. aegypti midgut prevent YFV-17D replication. Our study contributes to our basic understanding of vector-pathogen interactions and may also aid in the development of non-transmissible live virus vaccines.